The effect of shape on drag: a physics exercise inspired by biology. (8th June 2017) - Fingerut, Jonathan; Johnson, Nicholas; Mongeau, Eric; Habdas, Piotr
Abstract: As part of a biomechanics course aimed at upper-division biology and physics majors, but applicable to a range of student learning levels, this laboratory exercise provides an insight into the effect of shape on hydrodynamic performance, as well an introduction to computer aided design (CAD) and 3D printing. Students use hydrodynamic modeling software and simple CAD programs to design a shape with the least amount of drag based on strategies gleaned from the study of natural forms. Students then print the shapes using a 3D printer and test their shapes against their classmates in a friendly competition. From this exercise, students gain a more intuitive sense of the challenges that organisms face when moving through fluid environments, the physical phenomena involved in moving through fluids at high Reynolds numbers and observe how and why certain morphologies, such as streamlining, are common answers to the challenge of swimming at high speeds.